2007
DOI: 10.1007/s00330-006-0532-7
|View full text |Cite
|
Sign up to set email alerts
|

Neglectable benefit of searching for incidental findings in the Dutch--Belgian lung cancer screening trial (NELSON) using low-dose multidetector CT

Abstract: The purpose of this study was to prospectively determine the frequency and spectrum of incidental findings (IFs) and their clinical implications in a high risk population for lung cancer undergoing low-dose multidetector computed tomography (MDCT) screening for lung cancer. Scans of 1,929 participants were evaluated for lung lesions and IFs by two radiologists. IFs were categorised as not clinically relevant or possibly clinically relevant. Findings were considered possibly clinically relevant if they could re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 18 publications
1
79
1
6
Order By: Relevance
“…This prevalence is between that reported by other studies evaluating the incidental findings in lung cancer screening. In the DutchBelgian Randomised Controlled Lung Cancer Screening Trial (NELSON study) [7], signs of pulmonary fibrosis were reported in 117 (8%) out of 1,409 cases, whereas they were observed in six (1.3%) out of 449 cases recruited by the ProActive Lung Cancer Detection (PALCAD) study [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence is between that reported by other studies evaluating the incidental findings in lung cancer screening. In the DutchBelgian Randomised Controlled Lung Cancer Screening Trial (NELSON study) [7], signs of pulmonary fibrosis were reported in 117 (8%) out of 1,409 cases, whereas they were observed in six (1.3%) out of 449 cases recruited by the ProActive Lung Cancer Detection (PALCAD) study [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the thin-section CT features of these disorders have been increasingly described in the literature, few data have been reported on their significance in smokers participating in a lung cancer screening trial [7,8]. A comprehensive assessment of chest CT as a screening tool should include a thorough appreciation of the prevalence and nature of those findings that may have prognostic relevance and require therapeutic interventions.…”
mentioning
confidence: 99%
“…Incidental findings on thoracic CT are common [1]. Despite their wide range of clinical relevance, identifying such incidental findings may impose considerable impact on patient management and outcome [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore possible that analysis of imaging features other than lung nodules may have an impact on survival or other clinical outcomes. The relevance of these additional findings has been investigated by several groups [71,72,73]. In all of these studies the number of significant incidental findings did not exceed 7%.…”
Section: Technique and Algorithm Of Lung Nodule Assessmentmentioning
confidence: 84%